From Savings to Consumption: How Financial Literacy Influences College Students' Use of Electronic Wallets and Budgeting Behaviors - Kok Ban Teoh; Boon Keong Teow; Dwi Nita Aryani; Zhihan Liu; Yushuo Liu; Yifei Long; Jiahui Long; Rizkyvania Betarishanti Budiani; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
As mobile payments become increasingly prevalent in Asia, university students widely use electronic wallets for daily transactions, raising concerns about their financial management behavior. This study examines the effect of financial literacy on spending behavior, saving habits, and budgeting and e-wallet usage among university students. Data were collected from 150 respondents through an online survey. The findings indicate that financial literacy is negatively and significantly associated with spending behavior (r = –0.170, p 0.05) and positively associated with saving habits (r = 0.192, p 0.05). However, the relationship between financial literacy and budgeting and e-wallet usage is positive but not statistically significant (r = 0.116, p 0.05). Regression results show that financial literacy significantly reduces spending behavior (? = –0.159, p = 0.050), while its influence on budgeting behavior and e-wallet feature utilization is not significant. The model explains 6.7 percent of the variance (R² = 0.067). These findings suggest that financial literacy plays a protective role in controlling spending, but additional factors influence digital financial behavior.